4D printed assembly of sensors and actuators in complex formed metallic lightweight structures. (24th March 2023) - Weber, Rico; Kuhlow, Mathias; Spierings, Adriaan B.; Wegener, Konrad
Abstract: Powder bed fusion is an emerging additive manufacturing technique capable of producing complex formed metallic structures, which are not possible to manufacture with conventional manufacturing. These benefits of design freedom and manufacturability are often exploited in aerospace together with topology optimization to produce components with low mass and high stiffness. However, additive manufacturing is producing monolithic structures which lead to weakly damped resonant vibrations threatening e.g. space missions or are hazardous for mounted equipment. The integration of piezoelectric elements is the baseline for active and passive damping of these structures. This work presents a novel 4D printing integration approach exploiting the shape memory effect of NiTi as pre-stress actuation with low assembly and post-processing effort and high potential for shock absorptance. The influence on pre-stressing as the most significant requirement for piezoelectric stacks is investigated. An electronic pre-stress circuit was successfully validated to measure the pre-stress caused by the additively manufactured NiTi rod. Influence of piezoelectric stack design, speed of loading and thermal activation of the NiTi onto the pre-stress measurement is investigated. Finally, a pre-stress of 65 % of the specified allowable maximum from the piezoelectric stack manufacturer was achieved while exceeding the lower pre-stress limit.